Association between tobacco smoking and prognosis of occupational hand eczema: a prospective cohort study - Brans, Richard; Weisshaar, Elke; Scheidt, Reginald; Diepgen, Thomas L. (British journal of dermatology, 2014)
Background: Hand eczema (HE) is a common occupational skin disease. Tobacco smoking is known to be associated with adverse cutaneous effects. However, its influence on the prognosis of occupational HE has not yet been studied. Objectives: To evaluate relations between smoking status, severity and prognosis of occupational HE in patients taking part in an interdisciplinary tertiary individual prevention programme (TIP). Methods: In a prospective, multicentre, cohort study 1608 patients with occupational HE taking part in a TIP were recruited and followed up for 3 years. The clinical and self-reported outcome data of smokers and nonsmokers were compared. Results: Nonsmokers and smokers were equally distributed. During the TIP, the average self-reported daily cigarette consumption and the severity of HE decreased significantly (P < 0·01). However, at all time points HE was significantly more severe in smokers than in nonsmokers. This association was not dependent on the self-reported number of cigarettes smoked daily. Smokers had significantly more days of absence from work due to occupational HE than nonsmokers in the year before the TIP (P < 0·01) and in the following year (P = 0·02). After the TIP, smokers reported significantly more often that they had to give up their occupation (P = 0·02) than nonsmokers. Conclusions: The severity of occupational HE is increased in smokers. Tobacco smoking is associated with a higher number of days of absence from work and with not staying in the workforce owing to occupational HE. Thus, smoking confers a worse prognosis and interferes with the outcome of prevention programmes.
Gesehen am 25.08.2020